Iceberg sovereignty - Wood-Donnelly, Corine (Marine Policy, 2022)
Icebergs have a long history of commercial exploitation and while climate change has accelerated interest in Arctic resources, this enigmatic symbol of the region has received little attention in contemporary legal debates. In an age of growing freshwater scarcity, iceberg harvesting is currently unregulated and without legal status under international law beyond the rule of capture. Positioned at the intersection of water security and economic gain, icebergs are primed as a site for resource conflict. Framing the legal status of ice within historical debates, this paper considers principles of international law that could apply in determining rights derived from sovereignty over this resource. It posits a regulatory pathway via the Arctic Council, although the resource may in time simply disappear from both the legal and physical landscape. Iceberg sovereignty publishedVersion